ATMOSPHERIC AIR POLLUTION AND ITS MEDICO-ENVIRONMENTAL CONDITION - Mirzoyeva Istat Elmurodovna; Asadullaev Anwar Narzullaevich (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: The article will talk about the relationship between men and nature, the change in the composition and dynamics of the geographical shell as a result of the revolution of Science and technology, and the spread of diseases, types and preventive measures in regions with altered ecological status.